(untitled) (Palestine Technical College Journal for Research and Studies, 2021)
This study aimed to identify the role of applying human resources management strategies in achieving administrative creativity in Tripoli Medical Hospital from the point of view of the employees. The comprehensive enumeration method for all members of the study population; Due to the small size of the study population, it distributed the study questionnaire to all members of the study community, and (64) male and female employees responded, that is, a response rate of (84.21%), and the questionnaire was used as a data collection tool. The study reached a set of results, the most important of which are: The reality of the application of human resources management strategies in Tripoli Medical Hospital from the point of view of employees came with a large degree of approval, and a relative weight of (76.4%). and that the level of administrative creativity came to a large degree of agreement, with a relative weight of (75.5%). There is a statistically significant relationship between the strategies of human resource management and the achievement of administrative creativity in Tripoli Medical Hospital. There is also a statistically significant impact of human resource management strategies on administrative creativity. The study recommended that the hospital’s senior management should pay attention to all dimensions of human resource management strategies, and the elements that contribute to achieving administrative creativity.